Association of glyphosate exposure with frailty and all-cause mortality in general adults: A population-based cohort study - Tongtong Yang; Liuhua Zhou; Peng Jing; Yulin Bao; Lingfeng Gu; Yixi Chen; Xinying Shi; Hao Wang; Liansheng Wang; Sibo Wang (Ecotoxicology and Environmental Safety)
Background: Glyphosate is the most widely used herbicide globally. However, its association with frailty, an emerging public health concern, and mortality in the general population remains unclear. Methods: This cohort utilized the National Health and Nutrition Examination Survey (NHANES) 2013–2018 data, with follow-up through December 31, 2019. Weighted logistic regression, Cox regression, and restricted cubic splines analyses were performed to investigate the association of urinary glyphosate with frailty, defined using a 49-item frailty index at baseline, and all-cause mortality, respectively. Causal mediation analysis and sensitivity analysis were also employed. Results: 4697 adults (mean age: 47.1 years; 48.9 % male) were included. Multivariable logistic regression showed that elevated urinary glyphosate correlated with increased frailty prevalence (log2-transformed, adjusted OR = 1.14, 95 % CI: 1.04–1.25; quartiles, P for trend = 0.002), with a linear dose-response relationship (P value for nonlinearity = 0.568). During a median follow-up of 3.9 years, 238 total deaths occurred. Multivariable-adjusted Cox regression demonstrated that urinary glyphosate was positively related to all-cause mortality (log2-transformed, adjusted HR = 1.19, 95 % CI: 1.07–1.31; quartiles, P for trend = 0.005). Additionally, frailty significantly mediated the association between glyphosate and all-cause mortality, with mediation proportion of 30.3 %. Conclusions: Urinary glyphosate was positively associated with frailty and all-cause mortality in the general US adult population. Frailty also played a partial mediator role in this relationship. These findings provide new evidence of adverse health effects of glyphosate and imply that enhanced efforts should be made to mitigate exposure to glyphosate.